2008
DOI: 10.3132/pcrj.2008.00002
|View full text |Cite
|
Sign up to set email alerts
|

Subglottic stenosis as a complication of Wegener's granulomatosis

Abstract: Wegener's granulomatosis (WG) is a relatively uncommon collagen vascular disease that can lead to both upper and lower airway disease. Subglottic stenosis is one manifestation of the airway disease and can occur even during the quiescent phase of the disease, independent of an active inflammatory response. A high index of suspicion is necessary for this complication in patients with known WG who complain of dyspnoea, and WG should be high on the differential diagnosis in those found to have "idiopathic" subglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…The subglottis area is susceptible to symptomatic narrowing due to the complete ring of cricoids cartilage, whereas the lower trachea has a fibromembranous posterior wall. 6 It has been reported that the clinical course of SS runs independent of the systemic WG activity. SS can be present in absence of an active disease.…”
Section: Discussionmentioning
confidence: 99%
“…The subglottis area is susceptible to symptomatic narrowing due to the complete ring of cricoids cartilage, whereas the lower trachea has a fibromembranous posterior wall. 6 It has been reported that the clinical course of SS runs independent of the systemic WG activity. SS can be present in absence of an active disease.…”
Section: Discussionmentioning
confidence: 99%
“…SGS bei GPA sind das Ergebnis von Entzündungen, Ödemen und Fibrose, die sich unterhalb der Stimmbänder ereignen. Im Verlauf bildet sich fibrotisches Narbengewebe und es kommt zur fixierten Einengung des Lumens der Trachea [1,2,3]. Tendenziell erkranken mehr Frauen an subglottischen Stenosen [4,5].…”
Section: Introductionunclassified
“…3,4 Subglottic stenosis (SGS) is known to complicate Wegener's granulomatosis in 6-23% of cases and results from circumferential inflammation, oedema and fibrosis at the level of the cricoid cartilage, up to 4 cm below the vocal cords. 5,6 The effect of pregnancy on the course of Wegener's and associated SGS is unknown.…”
mentioning
confidence: 99%